Uma proposta de metodologia de ensino com analogias - Ronaldo Luiz Nagem; Dulcinéia Carvalhaes de Oliveira; Jully Anne Dias Yamauchi Teixeira (Universidade do Minho, 2001)
This paper presents a methodology for analogy-based teaching, a systematic approach for the utilization of this linguistic decive. Included in it are examples of Mathematical concepts about function. Seen here not only as a means to render understanding of concepts easier, but also as a tool for assessing learning results.